Density‐Dependent Metabolic Heterogeneity in Human Mesenchymal Stem Cells. (14th August 2015) - Liu, Yijun; Muñoz, Nathalie; Bunnell, Bruce A.; Logan, Timothy M.; Ma, Teng
Abstract Human mesenchymal stem cells (hMSCs) are intrinsically heterogeneous and comprise subpopulations that differ in their proliferation, multi‐potency, and functional properties, which are commonly demonstrated by culturing hMSCs at different plating densities. The objective of this study was to investigate the metabolic profiles of different subpopulations of hMSC by testing the hypothesis that the clonogenic hMSC subpopulation, which is selectively enriched in clonal density (CD) and low density (LD) culture (10 and 100 cells per square centimeter, respectively), possesses a metabolic phenotype that differs from that of hMSC in medium‐ or high‐density (MD: 1, 000 and HD: 3, 000 cells per square centimeter, respectively). Cells at CD and LD conditions exhibited elevated expression of CD146 and colony forming unit‐fibroblast compared with cells at MD‐ or HD. Global metabolic profiles revealed by gas chromatography‐mass spectrometry of cell extracts showed clear distinction between LD and HD cultures, and density‐dependent differences in coupling of glycolysis to the TCA cycle. Metabolic inhibitors revealed density‐dependent differences in glycolysis versus oxidative phosphorylation (OXPHOS) for ATP generation, in glutamine metabolism, in the dependence on the pentose phosphate pathway for maintaining cellular redox state, and sensitivity to exogenous reactive oxygen species. We also show that active OXPHOS is not required for proliferation in LD culture but that OXPHOS activity increases senescence in HD culture. Together, the results revealed heterogeneity in hMSC culture exists at the level of primary metabolism. The unique metabolic characteristics of the clonogenic subpopulation suggest a novel approach for optimizing in vitro expansion of hMSCs. Stem Cells2015;33:3368–3381